Differentiating Lithogenic Supplies, Water Mass Transport, and Biological Processes On and Off the Kerguelen Plateau Using Rare Earth Element Concentrations and Neodymium Isotopic Compositions - Grenier, Melanie; Garcia-Solsona, Ester; Lemaitre, Nolwenn; Trull, Thomas W.; Bouvier, Vincent; Nonnotte, Philippe; van Beek, Pieter; Souhaut, Marc; Lacan, Francois; Jeandel, Catherine (Frontiers in Marine Science, 2018)
Distributions of dissolved rare earth element (REE) concentrations and neodymium isotopic compositions (expressed as εNd) of seawater over and off the Kerguelen Plateau in the Southern Ocean are presented. The sampling took place during the austral spring bloom in October–November 2011 (KEOPS2 project, GEOTRACES process study) and aimed to further the investigations of the KEOPS1 austral summer study in terms of sources and transport of lithogenic material, and to investigate the impact of local biogeochemical cycles on the REE distributions. The REE signature of the coastal eastern Kerguelen Islands waters was characterized by negative europium anomalies (Eu/Eu*) and negative εNd in filtered samples. By contrast, the unfiltered sample showed a positive Eu/Eu* and more radiogenic εNd. These distinct signatures could reflect either differential dissolution of the local flood basalt minerals or differential leaching of local trachyte veins. The dissolved Kerguelen coastal REE patterns differ from those observed close to Heard Island, these latter featuring a positive Eu/Eu* and a less radiogenic εNd (Zhang et al., 2008). These differences enabled us to trace the transport of waters (tagged by the Kerguelen REE signature) 200 km downstream from the coastal area, north of the Polar Front. Northward transport of the central Plateau shallow waters, enriched by both local vertical supplies and lateral advection of inputs from Heard Island, was also evident. However, the transport of Kerguelen inputs southeastward across the Polar Front could not be discerned (possibly as a result of rapid dilution or scavenging of REE signatures), although evidence for such transport was found previously using Ra isotopes (Sanial et al., 2015). Comparison of the REE patterns at stations sampled prior, during and at the demise of the bloom revealed diverse fractionations, including production of significant lanthanum and europium anomalies, which are tentatively ascribed to chemical reactions with various inorganic and biogenic phases, including surface coatings, barite crystals, and biogenic silica.